Regulation of the growth performance and the gastrointestinal microbiota community by the addition of defective pear fermentation to feed of small-tailed Han sheep - Peng, Hongxin; Chen, Pinpin; Guo, Rui; Zhou, Zheng; Chen, Yafei; Xu, Ping; Su, Huawei; Xiao, Yuncai; Jiang, Hui (Frontiers in Microbiology, 2024)
This study investigated the effects of defective pear fermentation (DPF) diets on growth performance and gastrointestinal microbial communities in 60 healthy male small-tailed Han sheep, aged 90 days. The sheep were randomly divided into four groups, each consisting of three replicates with five sheep per replicate. Initially, all groups received a basal diet for seven days during the adaptation stage. Subsequently, for 60 days, group C (control) was fed a basal diet, group X received a basal diet with 2% DPF, group Y had a basal diet with 4% DPF, and group Z was fed a basal diet with 6% DPF. The results indicated that group Y experienced a significant increase in average daily gain (ADG) and average daily feed intake (ADFI). The addition of DPF significantly elevated the levels of GSH-Px and notably reduced MDA content compared to group C. Analysis of gastrointestinal microbiota showed that groups receiving DPF had increased relative abundances of Firmicutes and Ruminococcus_gauvreauii_group, and decreased abundances of Proteobacteria and Prevotella compared to group C. Analysis of gastrointestinal microbiota showed that groups receiving DPF had increased relative abundances of Lachnospiraceae_NK3A20_group, norank_f p-2534-设置了格式: 非突出显示 18B5_gut_group, Acetitomaculum, Actinobacteriota, Bacteroidota and Ruminococcus_gauvreauii_group, and decreased abundances of Proteobacteria, Prevotella, Staphylococcus and Psychrobacter compared to group C. Group X exhibited the highest relative abundance of Olsenella, while group Y showed a significant increase in unclassified_f Lachnospiraceae compared to the other groups. Bacterial function prediction indicated that pathways related to energy metabolism were more prevalent in group X and Y. This study preliminarily confirms the feasibility of using DPF as feed additives, providing a foundation for further research and evaluation of DPF's application in animal production. 2 设置了格式: 突出显示 设置了格式: 字体: (中文) +中文正文 (宋体), (中文) 简体中文 (中国大陆)